Cortesía y estatus en El libro de Apolonio (C. 151-241): códigos socioculturales y fórmulas de tratamiento - Mónica María Martínez Sariego (E-Spania)
The Libro de Apolonio was produced as an adaptation of the Historia Apollonii Regis Tyri to the preferences and habits of the Castilian society of the 13th century. The anonymous Spanish author was particularly skillful in adapting the source to the Hispanic socio-cultural context and to the new sensibility, as evidenced by the attention with which he deals with courteous and ceremonial details, including, but not limited to, linguistic aspects, such as pronominal and nominal forms of address. I analyze the linguistic, sociological and psychological aspects related to social uses and the rules that prescribe such uses in the central section of the book (c. 151-241), which covers from the arrival of the hero to King Architrastes’ court to his marriage with Luciana. These stanzas, which can be read as an autonomous section within the whole poem, portray delicate social situations solved by means of a proper management of courteous and linguistic codes.